Synthesis mechanisms on waste poplar fiber lightweight biomass bricks. (10th February 2020) - Zhang, Shuai; Dong, Rongdan; Wang, Meng; Jia, Wanda; Lu, Zeguang
Abstract: Upgrading waste poplar fiber into wooden brick is a green, eco-friendly strategy for waste wood-recovery and construction industry. In this work, waste poplar fiber is recycled into biomass brick with calcium hydroxide (Ca(OH)2 ) as the adhesive. The light-weight wooden bricks present novel features of light weight and environment-friendly. To study interaction mechanism between poplar fiber and Ca(OH)2, a series of tests are employed, including scanning electron microscopy, X-ray diffraction, infrared spectroscopy, nuclear magnetic resonance and so on. During the brick molding process, calcifications are generated and adhere closely on the surface of fiber. Poplar fiber and Ca(OH)2 connect with each other tightly through the generated calcification, and poplar fiber plays supporting and connecting role through the generated calcification, contributing to compressive strength of the wooden brick. The work is interesting on the preparation of wooden brick and the sustainable development of waste poplar fiber. Graphical abstract: Image 1 Highlights: Calcium hydroxide is used to produce the biomass brick with 70.15% volume percentage of poplar wood fiber. Poplar fiber connects with Ca(OH)2 matrix tightly through the generated calcifications. Poplar fiber plays supporting and connecting role through the generated calcification.